Sensing Estrogen with Electrochemical Impedance Spectroscopy - Jing Li; Byung Kun Kim; Kang-Kyun Wang; Ji-Eun Im; Han Nim Choi; Dong-Hwan Kim; Seong In Cho; Won-Yong Lee; Yong-Rok Kim (Journal of Analytical Methods in Chemistry)
This study demonstrates the application feasibility of electrochemical impedance spectroscopy (EIS) in measuring estrogen (17β-estradiol) in gas phase. The present biosensor gives a linear response (R2=0.999) for 17β-estradiol vapor concentration from 3.7 ng/L to 3.7 × 10−4 ng/L with a limit of detection (3.7 × 10−4 ng/L). The results show that the fabricated biosensor demonstrates better detection limit of 17β-estradiol in gas phase than the previous report with GC-MS method. This estrogen biosensor has many potential applications for on-site detection of a variety of endocrine disrupting compounds (EDCs) in the gas phase.